The Role of Halal Culinary Information on Social Media in Encouraging Purchase Intention of Pandeglang Regency Residents through the PLS-SEM Approach through Perceived Credibility - Rokhman; M. Sulaeman Jajuli (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of social media has changed the way consumers obtain and evaluate halal culinary information, particularly in the context of food purchasing decision-making in Pandeglang Regency. This study aims to analyze the influence of halal culinary information on social media on perceived credibility and purchase intention, and to examine the role of perceived credibility in driving purchase intention for halal culinary in Pandeglang Regency. This study uses a quantitative approach with the Structural Equation Modeling–Partial Least Squares (PLS-SEM) method. Data were collected through a survey of 142 respondents who are social media users and have experience accessing halal culinary information. The analysis results show that halal culinary information on social media has a positive and significant effect on perceived credibility and purchase intention for people in Pandeglang Regency. In addition, perceived credibility is also proven to have a positive and significant effect on purchase intention. These findings confirm that information credibility is an important mechanism that bridges halal culinary information on social media with consumer purchase intention in Pandeglang Regency. This study provides theoretical contributions to the development of halal marketing literature and practical implications for halal culinary entrepreneurs in designing credible and effective communication strategies through social media.